Basic Reproduction Number and Sensitivity Index Estimates from a Modified Deterministic Model for Nigeria COVID-19 Transmission - Davidson, Aromolaran A.; Okeke, Evelyn Nkiruka; David, Ikwuoche John (Kwaghe International Journal of Sciences and Technology, 2024)
Basic reproduction number and sensitivity index are necessary indices used in most epidemiological research to eval_uate the adequacy of formulated model. In this research, a modified deterministic model (MDM) of Covid-19 outbreak in Nigeria is formulated. The R0 is estimated alongside the SI to determine the acceptability of the formulated MDM. The analytic results showed that an R0 of 0.0000295 is obtained which imply the spread of the virus is under control. The SI result showed that 14 parameters of the MDM were sensitive whereby 8 of the parameters SI are positive while the remaining 6 parameters [natural mortality rate (μ), Proportion of asymptomatic that did not transit to symptomatic (v), natural mortality rate plus Covid-19 death induced (μ1), rate of vaccination (γ), rate of symptomatic being transferred to isolation (ϒ), transition of undetected exposed to quarantine (ф)] SI are negative. The SI result clearly showed that the significant negative indices parameters are responsible for reducing the R0 and enhanced the decline of the Covid-19 virus in Nigeria.